The influence of teaching experience, school location and academic background on teachers beliefs in teaching grammar - Samad, Arshad; Nurusus, Elisha (Canadian Center of Science and Education, 2015)
The beliefs that teachers hold regarding teaching will have a strong impact on the kinds of decisions that theymake in their classrooms. The type of materials, activities and instruction they will use in their lessons will beguided by these beliefs. At the same time, without having conviction in their beliefs about how students learn, itis difficult to imagine teachers being enthusiastic and effective in their teaching regardless of the approach theytake. In teaching English grammar to second language learners, teachers often subscribe to their own set ofpersonal beliefs that have been formed, most likely through their experience as well training. This applies as wellto the teaching of grammar which has had various competing points of view in terms of how it should be taught.This paper examines teachers’ beliefs using data collected from a survey administered to 345 English languageteachers in secondary schools in two states in Malaysia. A self-developed instrument was used to investigate fourdifferent emphases in the teaching of grammar in the classroom – input, explicit L2 knowledge, student outputand error correction – as proposed by Ellis (1998). The data was analysed according to how teaching experience,school location, and academic background can influence teachers’ views towards the importance of each of theseemphasis in teaching grammar. The results indicate a number of interesting points which can be of helpespecially in teacher training and professional development.